Optimizing Reversible Phase‐Transformation of FeS2 Anode via Atomic‐Interface Engineering Toward Fast‐Charging Sodium Storage: Theoretical Predication and Experimental Validation - Wenxi Zhao; Yanbing Zhou; Hao Zhou; Xinqin Wang; Shengjun Sun; Xun He; Yongsong Luo; Binwu Ying; Yongchao Yao; Xiaoqing Ma; Xuping Sun (Advanced Science)
Abstract Sodium‐storage performance of pyrite FeS2 is greatly improved by constructing various FeS2‐based nanostructures to optimize its ion‐transport kinetics and structural stability. However, less attention has been paid to rapid capacity degradation and electrode failure caused by the irreversible phase‐transition of intermediate NaxFeS2 to FeS2 and polysulfides dissolution upon cycling. Under the guidance of theoretical calculations, coupling FeS2 nanoparticles with honeycomb‐like nitrogen‐doped carbon (NC) nanosheet supported single‐atom manganese (SAs Mn) catalyst (FeS2/SAs Mn@NC) via atomic‐interface engineering is proposed to address above challenge. Systematic electrochemical analyses and theoretical results unveil that the functional integration of such two type components can significantly enhance ionic conductivity, accelerate charge transfer efficiency, and improve Na+‐adsorption capability. Particularly, SAs Mn@NC with Mn‐Nx coordination center can reduce the decomposition barrier of Na2S and NaxFeS2 to further accelerate reversible phase transformation of Fe/Na2S→NaFeS2→FeS2 and polysulfides decomposition. As predicted, such FeS2/SAs Mn@NC showcases outstanding rate capability and fascinating cyclic durability. A sequence of kinetic studies and ex situ characterizations provide the comprehensive understanding for ion‐transport kinetics and phase‐transformation process. Its practical use is further demonstrated in sodium‐ion full cell and capacitor with impressive electrochemical capability and excellent energy‐density output.